ELECTROCHEMISTRY CHARACTERIZATION OF FERROCENE/FERRICENIUM REDOX COUPLE AT GLASSYCARBON ELECTRODE - Neghmouche, N. S.; Khelef, A.; Lanez, T. (University of Eloued جامعة الوادي, 2009)
In the present work the oxidation of ferrocene, , to the ferrocenium cation, , was examined in the solvents dichloromethane, and aqueous ethanol using the technique of cyclic voltammetry. The anodic (Epa) and the cathodic (Epc) peak potentials, as well as the corresponding anodic (ipa) and cathodic (ipc) peak currents, were obtained at different scan rates (0.05, 0.10, 0.30, 0.50 V.s-1).Â The diffusion coefficients (D) have been calculated using the Randles-Sevcik equation. The effects of changing the scan rate on the electrochemical behavior of ferrocene have been examined.
Articale in Journal of fundamental and Applied Sciences Vol. 01 N. 02
Keywords: Cyclic voltammetry, diffusion coefficient, ferrocene, half-wave potential, Randles-Sevcik equation